Workers’ Education in Palestine - Elayassa, Wajih (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2013)
Due to the political context and the restrictions placed on general freedoms and trade union activities, workers’ education in Palestine remained informal and largely reliant on oral memory until the early 1990s. For decades, it was an integral part of political education. Workers’ education only became a stand-alone field after the establishment of the Palestinian Authority, when the change of circumstances enabled the Democracy and Workers’ Rights Centre in Palestine to focus on developing training materials and curricula specifically aimed at strengthening the Palestinian labour movement. First inspired and modelled on materials and courses taught internationally, the Centre’s labour education program has grown to encompass many locally produced materials and seeks to address specific challenges that face unions in Palestine.